Comparison between the experimental models to determine the maximum lateral pressure in self-compacting concrete - Teixeira, Sofía (2013)
The design of vertical formwork is dependent on the prediction of the maximum lateral pressure exerted by fresh concrete. This work describes the experimental models formulated in the bibliography to predict maximum lateral pressure exerted by Self-compacting concrete (SCC) on vertical formworks and it performs a comparison of them against two experimental cases recompiled from the bibliography; columns of major and small heights. Therefore, this article has two main objectives, firstly intent to justify the use of the models which need a rheological parameter to predict the maximum lateral pressure exerted by SCC, and secondly intent to determine the model that best fits to the maximum experimental lateralpressure.